2022
DOI: 10.1099/mic.0.001192
|View full text |Cite
|
Sign up to set email alerts
|

The respiratory lipoquinone, menaquinone, functions as an inducer of genes regulated by the Mycobacterium smegmatis repressor MSMEG_2295

Abstract: A previous study reported that the Mycobacterium smegmatis (Msm) protein MSMEG_2295 is a repressor controlling the expression of several genes, including that for MSMEG_5125, a putative isoprenoid binding protein belonging to the YceI family, and DinB2, a DNA damage repair enzyme. This repressor is encoded by the first gene of the operon that also expresses the gene for DinB2. Targeted inhibition of MSMEG_5125 using CRISPRi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In addition, recent studies revealed that the dinB2 expression is under the control of at least two TetR family proteins (Msmeg_6564 and Msmeg_2295), and their deletion and/or overexpression induce dinB2 expression ( Yang et al, 2012 ; Patra et al, 2021 ). Menaquinone, a respiratory lipoquinone, induces dinB2 expression more than 10-fold, by both inhibiting the Msmeg_2295 repression and acting as a direct inducer ( Barman et al, 2022 ). Other experimental conditions will need to be tested to assess the impact of dinB2 deletion on mutagenesis in mycobacteria, including during infection or after menaquinone treatment, to confirm the phenotypes demonstrated here which are derived from induced expression of DinB2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies revealed that the dinB2 expression is under the control of at least two TetR family proteins (Msmeg_6564 and Msmeg_2295), and their deletion and/or overexpression induce dinB2 expression ( Yang et al, 2012 ; Patra et al, 2021 ). Menaquinone, a respiratory lipoquinone, induces dinB2 expression more than 10-fold, by both inhibiting the Msmeg_2295 repression and acting as a direct inducer ( Barman et al, 2022 ). Other experimental conditions will need to be tested to assess the impact of dinB2 deletion on mutagenesis in mycobacteria, including during infection or after menaquinone treatment, to confirm the phenotypes demonstrated here which are derived from induced expression of DinB2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies revealed that the dinB2 expression is under the control of at least two TetR family proteins (Msmeg_6564 and Msmeg_2295), and their deletion and/or overexpression induce dinB2 expression (Yang et al , 2012; Patra et al , 2021). Menaquinone, a respiratory lipoquinone, induces dinB2 expression more than 10-fold, by both inhibiting the Msmeg_2295 repression and acting as a direct inducer (Barman et al , 2022). Other experimental conditions will need to be tested to assess the impact of dinB2 deletion on mutagenesis in mycobacteria, including during infection or after menaquinone treatment.…”
Section: Discussionmentioning
confidence: 99%